Impact of gentamicin coadministration along with high fructose feeding on progression of renal failure and metabolic syndrome in Sprague-Dawley rats - Ibraheem, Zaid O.; Basir, Rusliza; Aljobory, Ahmad Kh.; Ibrahim, Omar E.; Alsumaidaee, Ajwad; Yam, Mun Fee (Hindawi Publishing Corporation, 2014)
The current study evaluates the impact of high fructose feeding in rat model of gentamicin induced nephrotoxicity. Sprague-Dawley rats weighing 180-200 g were randomized into four groups; (C) received standard rodents chow with free access to ad libitum drinking water for 8 weeks and was considered as control, (F) received standard rodents chow with free access to drinking water supplemented with 20% (W/V) fructose for the same abovementioned period, (FG) was fed as group F and was given 80 mg/kg (body weight)/day gentamicin sulphate intraperitoneally during the last 20 days of the feeding period, and (G) was given gentamicin as above and fed as group C. Renal function was assessed at the end of the treatment period through measuring serum creatinine, uric acid and albumin, creatinine clearance, absolute and fractional excretion of both sodium and potassium, twenty-four-hour urinary excretion of albumin, and renal histology. For metabolic syndrome assessment, fasting plasma glucose and insulin were measured and oral glucose tolerance test was performed throughout the treatment period. Results showed that gentamicin enhances progression of fructose induced metabolic syndrome. On the other hand, fructose pretreatment before gentamicin injection produced a comparable degree of renal dysfunction to those which were given fructose-free water but the picture of nephrotoxicity was somewhat altered as it was characterized by higher extent of glomerular congestion and protein urea. Overall, more vigilance is required when nephrotoxic drugs are prescribed for patients with fructose induced metabolic syndrome.